Ongoing Initiatives to Improve the Quality and Efficiency of Medicine Use within the Public Healthcare System in South Africa; A Preliminary Study - Meyer, Johanna C.; Schellack, Natalie; Stokes, Jacobus; Lancaster, Ruth; Zeeman, Helecine; Defty, Douglas; Godman, Brian; Steel, Gavin (Frontiers in Pharmacology, 2017)
Introduction: South Africa has an appreciable burden of both communicable and non-communicable diseases as well as high maternal, neonatal and child morbidity. There have been significant strides with improving the public health system, and addressing current inequalities, in recent years with the right to health a constitutional provision in South Africa. Initiatives include the introduction of National Health Insurance (NHI), programmes to enhance access to medicines for patients with chronic diseases, as well as activities to improve care in hospitals including improving pharmacovigilance. Consequently, the objective of this paper is to review ongoing initiatives within the public healthcare sector in South Africa and their influence to provide future direction. Method: Principally a structured review of current and planned activities. Results: There have been a number of major activities and initiatives surrounding the availability and access to medicines in the public system in recent years in South Africa. This includes a National Surveillance Centre and an innovative early warning system for the supply of medicines as well as the development of a National Health Care Pricing Authority and initiatives to improve contracting. There have also been developments to improve the supply chain including instigating Medicine Procurement Units in the provinces and enhancing forecasting capabilities. Access to medicines is improving though the instigation of stable chronic disease management initiatives to increase the number of external pick-up points for medicines. There are also ongoing programmes to enhance adherence to medicines as well as enhance adherence to Standard Treatment Guidelines and Essential Medicines Lists with their increasing availability. In addition, there is a movement to enhance the role of health technology assessment in future decision making. Hospital initiatives include increased focus on reducing antimicrobial resistance through instigating stewardship programmes as well as improving adverse drug reaction reporting and associated activities. Conclusion: Overall, there are an appreciable number of ongoing activities within the public health system in South Africa to try and ensure and sustain universal healthcare. It is too early to assess their impact, which will be the subject of future research.